2017
DOI: 10.1016/j.bbr.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of stress and kappa opioid receptor activation on conditioned place aversion in male and female California mice

Abstract: Psychosocial stress leads to the activation of kappa opioid receptors (KORs), which induce dysphoria and facilitate depression-like behaviors. However, less is known about the long-term effects of stress and KORs in females. We examined the long-term effects of social defeat stress on the aversive properties of KOR activation in male and female California mice (Peromyscus californicus) using a conditioned place aversion paradigm. Female California mice naïve to social defeat, formed a place aversion following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 50 publications
(78 reference statements)
3
20
0
Order By: Relevance
“…Sal A has previously been shown to have no aversion in CTA experiments at 0.3 mg/kg [ 72 ], and conditioned place preference at low doses (0.1–40 μg/kg) but aversion at higher doses in rats (0.16–1 mg/kg) [ 105 , 106 ] and in mice (1–3.2 mg/kg) [ 63 ]. While we confirm the aversive properties of U50488 (10 mg/kg) ( Figure 8 a) seen in previous studies [ 104 ], Mesyl Sal B (0.3 mg/kg) had no effects on either place aversion ( Figure 8 b) or taste aversion ( Figure 8 c). Similar results were found for another more potent Sal A analogue, 2-ethoxymethyl ether Sal B (0.1 mg/kg), which did not show aversive effects in the CPA paradigm [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sal A has previously been shown to have no aversion in CTA experiments at 0.3 mg/kg [ 72 ], and conditioned place preference at low doses (0.1–40 μg/kg) but aversion at higher doses in rats (0.16–1 mg/kg) [ 105 , 106 ] and in mice (1–3.2 mg/kg) [ 63 ]. While we confirm the aversive properties of U50488 (10 mg/kg) ( Figure 8 a) seen in previous studies [ 104 ], Mesyl Sal B (0.3 mg/kg) had no effects on either place aversion ( Figure 8 b) or taste aversion ( Figure 8 c). Similar results were found for another more potent Sal A analogue, 2-ethoxymethyl ether Sal B (0.1 mg/kg), which did not show aversive effects in the CPA paradigm [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have used CPA to measure the aversive properties of the traditional KOPr agonists U69593 [ 101 , 102 , 103 ] and U50488 [ 104 ]. Sal A has previously been shown to have no aversion in CTA experiments at 0.3 mg/kg [ 72 ], and conditioned place preference at low doses (0.1–40 μg/kg) but aversion at higher doses in rats (0.16–1 mg/kg) [ 105 , 106 ] and in mice (1–3.2 mg/kg) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the overwhelming majority of preclinical studies on KOR antagonists have been conducted in male rodents (but see, Russell et al, 2014 ), so it is unclear whether these antagonists have similar properties in females. This is an essential question because women are almost twice as likely to develop depression as men ( Kessler, 2003 ), and sex differences in physiological responses to stress may affect risk for depression ( Bale and Epperson, 2015 ; Laman-Maharg et al, 2017 ). Second, most studies have focused on the short-term effects of KOR antagonists in stressful contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, social defeat stress induces KOR activation ( McLaughlin et al, 2006 ) and has been reported to increase time spent immobile in some cases ( Jin et al, 2015 ) but not others ( Krishnan et al, 2007 ). There is growing evidence that over a period of days or weeks, stressors such as defeat reduce the efficacy of KOR on behavior ( Al-Hasani et al, 2013 ; Laman-Maharg et al, 2017 ). Overall, while there is strong evidence that KOR antagonists have antidepressant-like effects in the force swim, the extent to which this effect generalizes to females or to females that have experienced stress is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…All drugs were dissolved in 100% DMSO and diluted in saline to the desired concentration (no DMSO concentration exceeded 5% v/v final). In drug combination experiments, nalfurafine was injected subcutaneously (sc) as described in the limited literature available regarding this compound's use in mice (Endoh et al, 1999;, while U50,488 and morphine were delivered by intraperitoneal (ip) injection as commonly described (Rada et al, 1996;McLaughlin et al, 2006;Koo et al, 2012;Muschamp et al, 2012;Laman-Maharg et al, 2017;Robinson et al, 2017). Dose range for nalfurafine and U50,488 were chosen based upon the place preference data in the literature Land et al, 2009b;Ehrich et al, 2015b).…”
Section: -Drugsmentioning
confidence: 99%